Evanescent Wave Cavity Ring-Down Spectroscopy as a Probe of Interfacial Adsorption: Interaction of Tris(2,2′-bipyridine)ruthenium(II) with Silica Surfaces and Polyelectrolyte Films - Powell, H; Schnippering, M; Mazurenka, M; Macpherson, J; Mackenzie, S; Unwin, P (American Chemical Society, 2008)
Evanescent wave cavity ring-down spectroscopy (EW-CRDS) has been used to study the interaction of the tris(2,2′-bipyridine)ruthenium(II) complex, [Ru(bpy)3]2+, at both native silica surfaces and surfaces modified with polyelectrolyte films. Both poly-l-lysine (PLL) and PLL/poly-l-glutamic acid (PGA) bilayer functionalized interfaces have been studied. Concentration isotherms exhibit Langmuir-type adsorption behavior on both silica and PGA-terminated surfaces from which equilibrium constants have been derived. The pH-dependence of the [Ru(bpy)3]2+ adsorption to silica and the PLL/PGA film has also been investigated. For the latter substrate, the effective surface pKa of the acid groups was found to be 5.5. The effect of supporting electrolyte was also investigated and was shown to have a significant effect on the extent of [Ru(bpy)3]2+ adsorption. A thin-layer electrochemical cell arrangement, in which a working electrode was positioned just above the substrate, was used to change the solution pH in a controlled way via the potential-pulsed chronoamperometric oxidation of water. By measuring the optical absorption using EW-CRDS during such experiments, the desorption of [Ru(bpy)3]2+ from the surface has been monitored in real time. Experiments were carried out at different cell thicknesses and at various pulse durations. By combining data from the EW-CRDS experiments with fluorescence confocal laser scanning microscopy (CLSM) to determine the pH at the substrate surface, the pKa of the PLL/PGA film could be ascertained and was found to agree with the static pH isotherm measurements. These studies provide a platform for the further use of electrochemistry combined with EW-CRDS to investigate dynamic processes at interfaces.